As percepções do processo de demissão e suas consequências no employer branding - Silva, Jessica Camila da; Lombardi, Wanessa Bonini Borges (Universidade Federal de São Carlos, 2022)
Given the current scenario and the increasingly complex and challenging human-vs-work relationships, both in the business and social spheres, the present work proposes to investigate the perceptions of professionals in termination processes for the company's Employer Branding. From a qualitative and quantitative approach, research and analysis were carried out through sampling, with the purpose of seeking common scenarios among the respondents. The main result was found in several points of the research carried out when the dismissed person was dissatisfied with the institution, whether in voluntary or involuntary dismissals.
Perceptions of the dismissal process and the consequences on employer branding
Keywords: Demissão; Employer branding; Desligamento; Trabalho; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS